Case report: A novel PPP3CA truncating mutation within the regulatory domain causes severe developmental and epileptic encephalopathy in a Chinese patient - Li, Jieling; Cao, Jie (Frontiers in Neurology, 2022)
Introduction: Developmental and epileptic encephalopathy 91 (DEE91) is a severe neurodevelopmental disorder caused by heterozygous PPP3CA mutations. As far as we know, only a few DEE91 cases were reported. Results: This study reports a boy who had recurrent afebrile convulsions and spasms at age 2 months. After being given multiple anti-epileptic treatments with levetiracetam, ACTH, prednisone, topiramate, clonazepam, his seizures were not completely relieved. At age four months, the patient had neuromotor developmental delayed with difficult feeding; at age six months, he had developmental regression with recurrent spasms and myoclonic seizures that could responded to vigabatrin. At age one year and four months, the patient had profound global developmental delay (GDD) with intermittent absence seizures. The whole exome sequencing (WES) identified a novel loss-of-function variant c.1258_c.1259insAGTG (p.Val420fs) in PPP3CA. Conclusion: This finding expands the genetic spectrum of PPP3CA gene and reinforces the theory that DEE91-associated truncating mutations clustering within a 26-amino acid region in the regulatory domain (RD) of PPP3CA.